2012
DOI: 10.1620/tjem.226.29
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Mesenchymal Stem Cells Preconditioned with Hydrogen Sulfide Enhances Repair of Myocardial Infarction in Rats

Abstract: Stem cell transplantation has become a promising therapeutic approach for the treatment of myocardial infarction (MI). However, the poor survival of the donor cells after transplantation has restricted its therapeutic efficacy. Hydrogen sulfide (H 2 S), one gaseous signaling molecule, has been applied to inhibit cell apoptosis and promote cell survival. In the present study, we therefore examined the effects of H 2 S on the survival of mesenchymal stem cells (MSCs). MSCs were isolated from the femur of male Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 38 publications
2
49
0
3
Order By: Relevance
“…H 2 S has been applied to inhibit cell apoptosis and promote cell survival in such cases. It has been demonstrated that H 2 S preconditioning effectively promotes stem cell survival under conditions of ischemic injury and helps cardiac repair after MI (92).…”
Section: H 2 S: a Novel Therapeutic Agent In Age-associated Diseases?mentioning
confidence: 99%
“…H 2 S has been applied to inhibit cell apoptosis and promote cell survival in such cases. It has been demonstrated that H 2 S preconditioning effectively promotes stem cell survival under conditions of ischemic injury and helps cardiac repair after MI (92).…”
Section: H 2 S: a Novel Therapeutic Agent In Age-associated Diseases?mentioning
confidence: 99%
“…These findings suggest that modulation of H 2 S metabolism may serve as a therapeutic approach to promote the viability of transplanted MSCs and facilitate MSC-based regeneration. Consistent with this, it was reported that H 2 S improves transplanted MSC survival in infarcted myocardium and aids in cardiac repair (Xie et al 2012). To further understand the role of H 2 S on transplanted MSCs and translate these findings from the bench top to the clinic, more studies of preclinical animal models are needed.…”
Section: H 2 S Regulates Msc Stemnessmentioning
confidence: 70%
“…H 2 S has recently been proposed as an endogenous mediator or inhibitor of cell apoptosis in various systems. H 2 S treatment could increase MSC proliferation and survival and attenuate hypoxia-, oxidant-, or serum deprivation-induced apoptosis (Fox et al 2012;Xie et al 2012;Zhao et al 2013;Li et al 2014;Aykan et al 2015;Guo et al 2015). Mechanically, H 2 S activates PI3K/Akt, Erk1/2, and GSK-3β (glycogen synthase kinase-3β) pathways to decrease hypoxia-induced MSC apoptosis.…”
Section: H 2 S Regulates Msc Stemnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial agent (s) delivery of Nanoparticle-medium into pathogen-containing intracellular vacuoles in macrophages could be useful and help to removing cellular reservoirs [19]. A simple one-step procedure to obtain CS-TPP and concomitant complexion with sodium alginate was implicated, to prepare trans mucosal formulations for the absorption of insulin [20]. Developed PLGA nanoparticles intended for the transdermal application of encapsulated glucosamine, which is a highly hydrophilic and poor permeable drug.…”
Section: Literature Surveymentioning
confidence: 99%